Unveiling the Nexus between Green Accounting, Environmental Performance, and Corporate Social Responsibility Disclosure for Profitability Maximization - Eka Sudarmaji; Iriana Medita Putri; Ismiriati nasip; Muslim Muslim; Amelia Oktrivina (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This research aimed to investigate the impact on profitability that Green Accounting, Environmental Performance, and Disclosure of Corporate Social Responsibility may have. This research examined the relationship between green accounting, environmental performance, CSR disclosure and ROA as a proxy of profitability. The research sample comprised 44 mining and industrial enterprises on the Indonesia Stock Exchange (IDX) for 2017-2020. The data analysis method used in this study is the panel data regression test. In this study, sample determination was carried out by purposive sampling method, namely sample determination using specific criteria to produce the sample as needed. Based on the model selection test that used the Chow and Hausman tests, it is possible to conclude that the most suitable fixed effect model is utilized in this research. According to the findings, only environmental performance and CSR disclosures were shown to have no substantial influence on the company's profitability. The research showed that investors and companies still had low perceptions of environmental performance and CSR disclosures and did not affect the company's financial performance. It was expected to increase the company's motivation to care more about its environment. In addition, investors were also expected to become more aware of the importance of environmental issues to increase the company's awareness to carry out CSR activities to maximize the positive impact and minimize the negative impact of such activities.